2011
DOI: 10.1002/anie.201103748
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Allylic Monofluoromethylation and Methylation of Morita–Baylis–Hillman Carbonates with FBSM and BSM by Cooperative Cinchona Alkaloid/FeCl2 Catalysis

Abstract: Working together: The title reactions were achieved in high yields with high ee values (see scheme, (DHQD)2AQN=hydroquinidine(anthraquinone‐1,4‐diyl) diether). The cooperative catalysis of bis(cinchona alkaloid) and Lewis acid, particularly FeCl2, was effective for these transformations and gave the monofluoromethylation products with over 90 % ee and methylation products with up to 97 % ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(26 citation statements)
references
References 91 publications
0
26
0
Order By: Relevance
“…Although there have been many reports on trichloromethylation reactions, enantioenriched trichloromethylated compounds attract less attention than others such as racemic compounds, and the method for direct enantioselective trichloromethylation is extremely rare . In recent years, we reported the enantioselective reactions of MBH‐acetates, carbonates, and fluorides with fluoromethylated nucleophiles under organocatalysis providing allylic monofluoro‐ and trifluoromethylated compounds in high yields with high enantioselectivities . During our research of the trifluoromethylation of MBH‐fluorides 1 with Me 3 SiCF 3 , we accidently noticed that allylic trichloromethylated compounds 2 were obtained predominantly instead of trifluoromethylated ones when the reaction was carried out in chloroform, HCCl 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Although there have been many reports on trichloromethylation reactions, enantioenriched trichloromethylated compounds attract less attention than others such as racemic compounds, and the method for direct enantioselective trichloromethylation is extremely rare . In recent years, we reported the enantioselective reactions of MBH‐acetates, carbonates, and fluorides with fluoromethylated nucleophiles under organocatalysis providing allylic monofluoro‐ and trifluoromethylated compounds in high yields with high enantioselectivities . During our research of the trifluoromethylation of MBH‐fluorides 1 with Me 3 SiCF 3 , we accidently noticed that allylic trichloromethylated compounds 2 were obtained predominantly instead of trifluoromethylated ones when the reaction was carried out in chloroform, HCCl 3 .…”
Section: Methodsmentioning
confidence: 99%
“…This provided chiral α-methylene β-monofluoromethyl esters with high ee’s of up to 97% (Scheme 128 ). 141 The transformation is envisaged to proceed by S N 2′ attack of the quinuclidine nitrogen atom of the cinchona alkaloid catalyst to afford a cationic intermediate, which is then attacked by the FBSM anion in another S N 2′ reaction to give the product (see section 3.1.8 for further discussion of this approach). The authors proposed a transition state model to account for the observed absoute stereochemistry and suggested that the conformation shown may be stabilized by π–π interations in the U-shaped cleft of the (DHQD) 2 AQN (Figure 25 ).…”
Section: Catalytic Enantioselective Monofluoromethylationmentioning
confidence: 99%
“…10 They reported that the use of FeCl 2 or Ti(O i Pr) 4 increase the enantioselectivity of their reaction but it was not crucial for reactivity.…”
Section: Q5mentioning
confidence: 99%